Translation Analysis of Culture-Specific Items (CSIs) in the Indonesian Movie “KKN di Desa Penari” - Dominggus Florensius; Bahing Siritman; Richard Ferry Nugraha; Arvin Armando; Arya Febridinata (Journal of English Language and Education, 2026)
Translation of Culture-Specific Items (CSIs) in audiovisual media plays a crucial role in supporting cross-cultural understanding and preserving cultural meaning. However, previous studies have predominantly focused on translation strategies, with limited attention to how translated CSIs contribute to cultural understanding among global audiences, as evaluated through the extent to which the translations preserve referential meaning, retain cultural nuances, and remain comprehensible to target viewers. This study aims to analyze the translation of CSIs in the Indonesian horror film KKN di Desa Penari by applying Newmark’s (2010) CSI categories and Aixelá’s (1996) translation strategy framework. This research employs a qualitative descriptive case study design. The data were collected from movie dialogues and their English subtitles using observation and note-taking techniques. The analysis identified 41 CSIs classified into six categories, with social life and private passions emerging as the most dominant. The findings also reveal that while many translations successfully preserve referential meaning, some cultural nuances are reduced in the process. This study contributes to audiovisual translation research by highlighting the role of CSI translation not only as a linguistic process but also as a mediator of cultural understanding. It shows that although translation enables international audiences to access Indonesian cultural elements, certain layers of cultural depth may not be fully conveyed.